Successful Treatment of Recalcitrant Hidradenitis Suppurativa with Adalimumab - Ian Gorovoy; Adar Berghoff; Laura Ferris (Case Reports in Dermatology, 2009)
Hidradenitis suppurativa is a chronic disease that affects the apocrine gland-bearing regions of the body. The etiology of this disorder is poorly understood, but most likely is a complex process involving follicular apocrine occlusion with subsequent perifolliculitis. Many treatment options have been reported with varying degrees of success, including topical and oral therapy and surgical procedures. Recently, TNF-α antagonists have been reported as effective therapy in a few patients. We report here a patient who initially responded to infliximab but developed an infusion reaction to this medication. After subsequent treatment with adalimumab, the patient’s disease improved dramatically and has been maintained under excellent control for over 15 months. We propose that TNF-α inhibitors, particularly monoclonal antibody based agents, are a viable treatment option in patients with severe, recalcitrant HS and that a patient may be safely and successfully treated with the fully human monoclonal antibody adalimumab in cases in which the chimeric monoclonal antibody infliximab therapy is not tolerated.